Structural and Biocidal Studies of Monobutyltin (IV) Derivatives of 1-Hydroxy-2-Naphthoic Acid - Mittal, Pankaj; Pachouri, Manoj Kumar (Challenges and Advances in Chemical Science Vol. 6, 2021)
Organotin compounds are well known to exhibit biocidal properties such as antibacterial, antifungal as well as antipestal activities. A few organotin (IV) derivatives have been synthesized in 1:1 [BuSn(L)(OPri)] 1:2 [BuSn(LH)2(OPri)], 1:3 [BuSn(LH)3] and 2:1 [(BuSn)2L(OPri)4] molar ratios (where L = 1-Hydroxy-2-naphthoic acid) by the reaction between monobutyltin triisopropoxide and 1-Hydroxy-2-Naphthoic acid. The synthesized derivatives were examined by elemental analyses as well as IR and NMR instrumental techniques. The derivatives were screened for antibacterial and antifungal activities by knowing Minimum Inhibitory Concentration (MIC) values on gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria as well as Aspergillus niger and Candida albicans fungi respectively. The compounds were also screened for antipestal activities against the pest Tribolium castaneum. These derivatives have shown enhanced biocidal activities than the corresponding ligand.